2022
DOI: 10.1590/s1677-5538.ibju.2022.0381
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between primary monosymptomatic enuresis and process toilet training: a case-control

Abstract: Objective: Primary monosymptomatic nocturnal enuresis (PMNE) is a prevalent condition in childhood, and the pathophysiology is multifactorial. This study investigated the relationship between the toilet training process (TT) and PMNE in children and adolescents. Patients and Methods: A case-control study was carried out from 2015 to 2020. The presence of PMNE was identified according to International Children's Continence Society criteria. A semi-structured questionnaire was applied to assess TT. Results: The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
3
0
4
Order By: Relevance
“…Control of elimination was carried out by the cerebral cortex which is responsible for facilitating and inhibiting the micturition reflex (Griffiths, 2015;Netto et al, 2020). To be able to perform these abilities a child needs to go through a complex process that is influenced by anatomical, physiological, and cultural factors (Carvalho et al, 2022). Apart from depending on the maturation and rate of child development, the success of TT is influenced by the support of parents, especially mothers who act as caregivers for children (Lestari et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Control of elimination was carried out by the cerebral cortex which is responsible for facilitating and inhibiting the micturition reflex (Griffiths, 2015;Netto et al, 2020). To be able to perform these abilities a child needs to go through a complex process that is influenced by anatomical, physiological, and cultural factors (Carvalho et al, 2022). Apart from depending on the maturation and rate of child development, the success of TT is influenced by the support of parents, especially mothers who act as caregivers for children (Lestari et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…27 Murillo et al 28 found no relationship between the age of starting toilet training and lower urinary tract dysfunction or constipation. Carvalho et al 29 also found no difference between the groups regarding the onset age of toilet training and occurrence of nocturnal enuresis. In our study, urinary retention during play and nocturnal enuresis were more frequent in the children who were toilet trained at 25-36 months of age.…”
Section: The Relationship Between Sociodemographic Features and The A...mentioning
confidence: 99%
“…Em virtude dos benefícios da amamentação, tanto para mãe quanto para o bebê, a Organização Mundial da Saúde (OMS) e o Ministério da Saúde (MS) recomendam que todas as mães amamentem seus filhos de forma exclusiva nos primeiros seis meses de vida, e após essa idade, deverá ser introduzida alimentação complementar apropriada, continuando, entretanto a amamentação até pelo menos os 2 anos de idade ou mais. Carvalho et al (2022) e Tarso (2021) evidenciaram que as crianças que realizaram o aleitamento materno exclusivo (AME), fazendo a correta inserção da introdução de alimentos nutritivos após os seis primeiros meses de vida em associação ao AM, apresentaram um melhor desenvolvimento do sistemas estomatognático e boa tonicidade da musculatura perioral quando comparadas às crianças que não foram amamentadas de formas exclusivas até os 12 meses de vida, por exemplo.…”
Section: Metodologiaunclassified
“…Amamentar não é um ato simples; é uma ação complexa que envolve questões sociais, biológicas, psicológicas e culturais. Sendo imprescindível iniciar o processo de orientação durante o pré-natal, ressaltando a importância da amamentação e seus benefícios, uma vez que o leite materno é capaz de nutrir o recém-nascido perfeitamente, promovendo hidratação, transmitindo anticorpos e também auxiliando a desenvolver vínculos de afeto entre o bebê e a mãe, firmando ainda mais esse binômio (Carvalho et al, 2022). De acordo com Silva et al (2018), é indubitável afirmar que por mais surpreendentes que sejam os avanços nas tecnologias de produção, processamento, conservação e preparo de alimentos, o leite materno continua sendo o alimento mais recomendado e de primeira escolha para crianças nos primeiros meses e anos de vida, sendo consenso internacional a inexistência de um substituto ideal para o Aleitamento Materno (AM), assim é afirmado que a amamentação é uma prática que traz benefícios tanto para mãe quanto para o filho.…”
Section: Introductionunclassified

Estudos Multidisciplinares Sobre Saúde Da Criança E Do Adolescente

RIBEIRO DE SOUSA,
MARQUES DAS CHAGAS,
EDUARDO DA SILVA BARBOSA
et al. 2023